May Measurement Month 2017: the results of blood pressure screening of 14 845 individuals in Kenya—Sub-Saharan Africa. (24th April 2019) - Ogola, Elijah N; Barasa, Felix; Barasa, Anders L; Gitura, Bernard M; Njunguna, Benson; Beaney, Thomas; Xia, Xin; Poulter, Neil R
Abstract: Elevated blood pressure (BP) is a growing burden worldwide leading to over 10 million deaths each year. Sub-Saharan Africa has the highest age-adjusted prevalence of hypertension. In Kenya, 24.5% of adults have elevated BP with lack of awareness being the main barrier to achieving satisfactory control rates. May Measurement Month (MMM17) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2017. Screening was coordinated by the Kenya Cardiac Society in 17 sites across the country. Blood pressure measurements, the definition of hypertension and statistical analysis followed the standard MMM protocol. A total of 14 847 individuals were screened. After multiple imputation, 3647 (24.6%) had hypertension. Of individuals not receiving any antihypertensive medication, 2019 (15.3%) were hypertensive. Of individuals receiving antihypertensive medication, 740 (45.5%) had uncontrolled BP. Being diabetic and having a body mass index (BMI) ≥25 kg/m 2 were associated with higher BP. Lack of awareness and poor control in those identified is a major challenge in Kenya. The MMM project demonstrated that mass screening for elevated BP is feasible, even in settings with limited resources. The presence of hypertension in a quarter of Kenyan adults with poor awareness and control rates demonstrates the need for programmes to raise awareness in the community.